2015
DOI: 10.1002/mnfr.201400688
|View full text |Cite
|
Sign up to set email alerts
|

A gut microbial metabolite of ginsenosides, compound K, induces intestinal glucose absorption and Na+/glucose cotransporter 1 gene expression through activation of cAMP response element binding protein

Abstract: Scope:The Na + /glucose cotransporter 1 (SGLT1) plays a crucial role in glucose uptake in intestinal epithelial cells (IECs), which has been shown essential in ameliorating intestinal inflammation. Ginseng has historically been used to treat inflammatory disorders. Understanding the regulatory mechanism of ginseng-mediated induction of SGLT1 gene expression in human intestinal cells is therefore important. Methods and results:We demonstrate that ginsenoside compound K (CK) enhances SGLT1-mediated glucose uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Indeed, attempts to suppress cancer cells by targeting this protein pair have been made. It was found that some compounds from a natural anti-cancer medicinal plant Panax ginseng concurrently suppressed EGFR and SGLT1 in a CREB-associated mechanism 40,41. Co-inhibition of EGFR and SGLT1 obtained an optimal outcome in suppressing prostate cancer compared with EGFR inhibitor alone.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, attempts to suppress cancer cells by targeting this protein pair have been made. It was found that some compounds from a natural anti-cancer medicinal plant Panax ginseng concurrently suppressed EGFR and SGLT1 in a CREB-associated mechanism 40,41. Co-inhibition of EGFR and SGLT1 obtained an optimal outcome in suppressing prostate cancer compared with EGFR inhibitor alone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of CK as BSA-CK NPs [ 39 ] and CK-conjugated superparamagnetic iron oxide nanoparticles [ 58 ], has been shown to have anti-inflammatory activity against RAW 264.7 cells induced by LPS. In another study, CK-mediated modulation of sodium/glucose cotransporter one via the epidermal growth factor receptor (EGFR) pathway was found to reduce intestinal inflammation [ 59 ].…”
Section: Health-promoting Activitiesmentioning
confidence: 99%
“…The sequences of DNA primers for PCR are listed in Table 1. Subsequently, serial 59-deletions and site mutations of the SGLT1 promoter were generated by PCR to obtain the SGLT1 (21560/122), (2500/122), (2235/122), (2169/122), (2136/122), (283/122), (227/122), and (mutant CRE) luciferase reporter plasmids as previously described (Martin et al, 2000;Wang et al, 2015). The sequence and orientation of the individual luciferase reporter constructs were confirmed by restriction mapping and DNA sequence analysis.…”
Section: D-[mentioning
confidence: 99%